2015
DOI: 10.1103/physrevlett.114.031301
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Wave Consistency Relations for Multifield Inflation

Abstract: We study the tensor spectral index nt and the tensor-to-scalar ratio r in the simplest multifield extension to single-field, slow-roll inflation models. We show that multifield models with potentials V ∼ i λi|φi| p have different predictions for nt/r than single-field models, even when all the couplings are equal λi = λj, due to the probabilistic nature of the fields' initial values. We analyze well-motivated prior probabilities for the λi and initial conditions to make detailed predictions for the marginalize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 61 publications
7
42
0
Order By: Relevance
“…These models can make universal landscape predictions based in part on the universality of N-flation [24]. A similar predictivity has been found in recent many-field numerical investigations in other contexts [14,15,25,26]. It is the goal of this paper to elucidate these simple predictions of manyfield models and investigate their prior dependence.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…These models can make universal landscape predictions based in part on the universality of N-flation [24]. A similar predictivity has been found in recent many-field numerical investigations in other contexts [14,15,25,26]. It is the goal of this paper to elucidate these simple predictions of manyfield models and investigate their prior dependence.…”
supporting
confidence: 68%
“…The method to obtain a random point includes sampling from the multi-variate distribution N (0, 1) and then dividing by the norm of the vector. Assuming that the φ i 's are uncorrelated with the masses (including the time dependent term e −2λiτ * ) and employing similar techniques as [25], one can show that at the limit of infinite number of fields the ratio in Eq. (4) is normally distributed with mean…”
mentioning
confidence: 99%
“…The regime of many-field inflation (N 10) typically yields a range of predictions for curvature perturbations at the end of inflation that is surprisingly easy to categorize in comparison to the apparently large dimensionality of parameter space (see e.g. Refs [40][41][42][43][44][45][46][47][48], though stochastic effects can be important in the presence of many fields [49]). Scenarios with many fields also tend to predict an amount of isocurvature perturbations at the end of inflation which increases with the number of fields [42,47], thereby elevating the importance of studying the effects of reheating for these models.…”
Section: Introductionmentioning
confidence: 99%
“…VI with N = 5 fields with kpiv = 0.05 Mpc −1 . Colored circles show the results from simulations for a particular choice of decay rates Γi, chosen as described in text following Eq (44)…”
mentioning
confidence: 99%
“…In the case of manyfield inflation, numerical studies of a specific model of n-flation in Refs. [31,43,46] found that models consisting of O(100) fields had similar predictive power to single field models 8 . This is despite the fact that for a modest number of fields 1 < n 10 the model is less predictive.…”
Section: Predictivity Of the Model Or Concentration Of Measurementioning
confidence: 99%